NANGGROE ACEH DARUSSALAM MENUJU PROVINSI HIJAU: PELUANG DAN TANTANGAN (Nanggroe Aceh Darussalam toward Green Province : Opportunity and Obstacle) - Ricky Avenzora (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
In order to support the new wave of environmental movement in Nanggroe Aceh Darussalam, so called the logging moratorium and green province, a three months qualitative study has been taken. The study has been aimed to find the recent dynamic of some stake holders those potentially play important role to achieve the green vision. The result shows that the capacity of human resources, and the social-dynamic of post-conflict community becoming a crucial variabels to drive an efficient and effective green movement mission.Keywords: Illegal logging, moratorium, green province, Nanggroe Aceh Darussalam, social dynamic.